2021
DOI: 10.1108/jarhe-05-2021-0183
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and accounting education: perspectives of undergraduate accounting students in Saudi Arabia

Abstract: PurposeThe purpose of this study is to explore undergraduate accounting students' perceptions and understanding of the concept of sustainable development. Moreover, this study aims to explore students' perceptions of the integration of sustainable development issues in accounting education in Saudi Arabia as an emerging country.Design/methodology/approachA questionnaire survey was administered to a sample of accounting students from four Saudi universities. The questionnaire contained five groups of questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
1
18
1
Order By: Relevance
“…For Saudi companies, they must reconsider the extent of their social practices and strike a balance between financial and nonfinancial goals, especially as a large number of recent studies indicate a positive and significant relationship between CSR practices and the financial performance of companies and that the integration of social responsibility practices in company strategy enables the company to achieve a sustainable competitive advantage (Rahi et al , 2022; Pham et al , 2021). For those responsible for accounting education in Saudi Arabia, the results of this study confirm the results of a number of recent studies that indicate the weakness of integrating sustainability issues, including environmental and social practices, into the accounting education curricula in Saudi universities (Ebaid, 2021). This requires a review of these curricula that focus on the shareholders theory rather than the stakeholders theory and teach accounting students that the main objective of the company is to maximize the shareholders' wealth without addressing the impact of business on the environment and society in which the company operates.…”
Section: Discussionsupporting
confidence: 85%
“…For Saudi companies, they must reconsider the extent of their social practices and strike a balance between financial and nonfinancial goals, especially as a large number of recent studies indicate a positive and significant relationship between CSR practices and the financial performance of companies and that the integration of social responsibility practices in company strategy enables the company to achieve a sustainable competitive advantage (Rahi et al , 2022; Pham et al , 2021). For those responsible for accounting education in Saudi Arabia, the results of this study confirm the results of a number of recent studies that indicate the weakness of integrating sustainability issues, including environmental and social practices, into the accounting education curricula in Saudi universities (Ebaid, 2021). This requires a review of these curricula that focus on the shareholders theory rather than the stakeholders theory and teach accounting students that the main objective of the company is to maximize the shareholders' wealth without addressing the impact of business on the environment and society in which the company operates.…”
Section: Discussionsupporting
confidence: 85%
“…Also, the study added that interpersonal and personal skills such as communication skills, were also needed for the execution of accounting task. Similarly, Ebaid (2021) added that aside the ranking of some technical skills as vital for the accounting profession, the profession also places high importance on the acquisition of key generic skills which includes professionalism in conduct, interpersonal and personal skills. This view is also shared by Ghani et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that information technology, interpersonal and personal skills were the most desired skills needed in the workspace of accounting graduates. Ebaid (2021) conducted a similar study in Saudi Arabia on the required employability skills of accounting graduates. It was revealed that both technical and generic skills were deemed important for the accounting job space.…”
Section: Introductionmentioning
confidence: 99%
“…The singleitem question considered as the dependent variable is widely used by previous studies (Chen and Takeuchi, 2011;Gutter and Copur, 2011;Halko et al, 2012;Phung et al, 2021). Five demographics are added in the model by previous studies (Henry et al, 2001;Jorgensen and Savla, 2010;Lusardi et al, 2010;Schr€ oder et al, 2011;Bottazzi and Lusardi, 2020;Ebaid, 2021).…”
Section: Methodsmentioning
confidence: 99%